Significados e sentidos do futebol feminino para as juventudes atendidas pela Estação Juventude em Sobral-CE. - Pinto, Leidiana do Nascimento (2022)
The work starts from the discovery, verified by studies, that the Public Policies for youth, built to meet the demands and aspirations of young people in Brazil, have not fostered a significant discussion of the themes that cross the daily lives of young people. The research defends the idea that public youth policies should be for youth, with and for youth in a fundamental perspective of participation. The work studies senses and meanings of women's football for youths attended by the youth station in Sobral - CE. It analyzes the perceptions that young people have in relation to women's football; identifies the reflections that young people make about their participation in the youth station; investigates the main contents played by young people. Its theoretical framework is the Public Policy for youth and women in the last 15 years, with an emphasis on health and sport. It was organized as an exploratory field research with a qualitative approach. As the main methodological strategy, it performs thematic analysis, through critical discourse analysis, empirically through interviews with the participants. The survey results are divided into three main themes, in addition to the analysis of the socioeconomic profile. The evaluation carried out on the profile of young people served by the EJ points to a scenario of poverty and social inequality, considering that 54.6% do not have their own home and more than 80% are brown and black, in addition to low wages that do not reach R$ 2,000.00. The theme of the speeches produced by the youth highlights the importance of social projects and the need to ensure mechanisms that guarantee the rights of youth, especially in the areas of education, work and health. Several important elements were pointed out about the perceptions of participation from the perspective of youths. The new forms of participation; the ability of young people to read socially; the ability to practice coresponsibility with the EJ space and the need for specific demands for young people. Regarding the theme reflections on gender, it points to the improvement of EJ, since the equipment reinforces heteronormativity, prioritizing and encouraging sports actions only for boys; the need to delve deeper into transversal themes, respecting the trajectories and diversities of young people.